THE ROLE OF WOMEN'S PERSONNEL IN THE DEVELOPMENT OF THE NATIONAL ECONOMY OF UZBEKISTAN: SOCIAL AND POLITICAL STATUS (1917-1940) - Kurbanova Nargiza Nasridinbekovna (Journals Park Publishing, 2022)
This article describes the colonial nature of the policy pursued by the Soviet regime to involve women in socio-political life and the factors and causes of the problems in this area, the socio-material status of women, the way of life on the basis of scientific sources.
Keywords: Soviet system; communist ideology; industrialization